Repurposing the domestic organic waste into green emissive carbon dots and carbonized adsorbent: A sustainable zero waste process for metal sensing and dye sequestration. Issue 5 (October 2021) - Das, Manita; Thakkar, Harshil; Patel, Divyesh; Thakore, Sonal
Abstract: This work reports a one pot facile route for complete valorization of domestic organic waste into biogenic carbon dots (BCDs) and biochar for application as nanosensor and adsorbent respectively. Among the various precursors used, dried rose petals derived (BCDRP ) and ripe banana peel derived (BCDBP ) carbon dots demonstrated quantum yields comparable to other previously reported biomass derived green fluorescing carbon dots. The BCDs exhibited sizes < 10 nm and excellent photo-stability upto 30 days with respect to different irradiation times as well as ionic strength. The BCDs were assessed for their optical performance and employed as fluorescent sensor for detection of heavy metal ions. The semi-quantitative and quantitative studies shows that BCDRP was selective towards Cr 6+ whereas BCDBP detected Fe 3+ in a mixture of metal ions. LOD values in pM range (81 pM for Cr 6+ in presence of BCDRP and 121 pM for Fe 3+ in presence of BCDBP ) advocates their high sensitivity. The real sample analyzing potential of the BCDs with excellent recoveries and minimal RSD suggest their successful practical applicability. For circular economy, the biochar formed as a byproduct was reused as an adsorbent for removal of cationic and anionic dyes with > 90% removal efficiencies. This protocol ensures a complete repurposing of organic waste into modified materials via a zero waste process as demonstrated by its schematic life cycle inventory chart. Graphical Abstract: ga1 Highlights: Domestic organic waste derived N & S co-doped green emissive carbon nanodots. Fluorescent nanodots selectively detected Cr 6+ and Fe 3+ in a mixture of metal ions. Low limits of detection (in pM range) and > 85% recovery in real sample analysis. Biochar obtained as byproduct of nanodot synthesis effective adsorbent for dyes. Life cycle inventory predicts the process to have minimal carbon footprints.